Nanoantenna-enhanced infrared spectroscopic chemical imaging - Kühner, Lucca; Vogt, Jochen; Huck, Christian; Neubrech, Frank (ACS sensors, 2017)
Spectroscopic infrared chemical imaging is ideally suited for label-free and spatially resolved characterization of molecular species, but often suffers from low infrared absorption cross sections. Here, we overcome this limitation by utilizing confined electromagnetic near-fields of resonantly excited plasmonic nanoantennas, which enhance the molecular absorption by orders of magnitude. In the experiments, we evaporate microstructured chemical patterns of C60 and pentacene with nanometer thickness on top of homogeneous arrays of tailored nanoantennas. Broadband mid-infrared spectra containing plasmonic and vibrational information were acquired with diffraction-limited resolution using a two-dimensional focal plane array detector. Evaluating the enhanced infrared absorption at the respective frequencies, spatially resolved chemical images were obtained. In these chemical images, the microstructured chemical patterns are only visible if nanoantennas are used. This confirms the superior performance of our approach over conventional spectroscopic infrared imaging. In addition to the improved sensitivity, our technique provides chemical selectivity, which would not be available with plasmonic imaging that is based on refractive index sensing. To extend the accessible spectral bandwidth of nanoantenna-enhanced spectroscopic imaging, we employed nanostructures with dual-band resonances, providing broadband plasmonic enhancement and sensitivity. Our results demonstrate the potential of nanoantenna-enhanced spectroscopic infrared chemical imaging for spatially resolved characterization of organic layers with thicknesses of several nanometers. This is of potential interest for medical applications which are currently hampered by state-of-art infrared techniques, e.g., for distinguishing cancerous from healthy tissues.
Gesehen am 27.11.2018